Inclusion of microbial inoculants with straw mulch enhances grain yields from rice fields in central China. (12th July 2020) - Wang, Lei; Qin, Tao; Liu, Tianqi; Guo, Lijin; Li, Chengfang; Zhai, Zhongbing
Abstract: Slow decomposition of crop straws under field conditions affects sowing and emergence of rice. Microbial inoculants can be used to promote crop straw decomposition for solving these problems and thus have been adopted for rice cultivation in China. However, its effect on greenhouse gas (GHG) emissions and grain yields remains unclear. Here, a two‐year field experiment was conducted to assess the effects of different straw returning methods (no straw, preceding crop straw mulch on the soil or incorporation into the soil, and straw mulch with microbial inoculants or straw incorporation with microbial inoculants) on GHG emissions and grain yields from rice fields in central China. Straw returning treatments significantly enhanced higher CH4 emissions by 21.1%–39.6% relative to no straw treatment, but did not affect N2 O emissions. Compared with straw mulch treatments, straw incorporation treatments significantly increased higher dissolved organic C (DOC) content by 20.0%–30.4% and mcrA abundance by 28.01%–37.3%; significant relationships of CH4 emissions with DOC content and mcrA abundance were observed. These resulted in 13.2%–16.0% higher CH4 emissions under straw incorporation treatments. Straw incorporation did not affect N2 O emissions relative to straw mulch due to similar mineral N contents. The application of inoculants showed no effects on CH4 and N2 O emissions, whereas it significantly enhanced the grain yields by 6.0%–9.1% and thus decreased GHG intensity (GHGI) by 4.3%–11.87%. Straw mulch with decomposing inoculants treatment resulted in the lowest global warming potential (GWP) and GHGI and the highest grain yield among all straw returning treatments. Taken together, our results indicate that mulch of straws with microbial inoculants on the soil is an effective measure to achieve a balance between the mitigation of GWP and the increase in grain yields from rice fields in central China. Abstract : This paper focused on assessing the effects of different straw managements (no straw, preceding crop straw mulching on the soil (SM) or incorporation into the soil (SI), and SM with decomposing inoculants (SMD) or SI with decomposing inoculants (SID)) on GHG emissions and grain yields from rice fields in central China.